SEVERITY INDEX IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Uralov Rustam Sherbekovich; Eshmuratov Sardor Eldorovich (Journals Park Publishing, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multiple organ damage and variable symptoms. SLE is characterized by alternating periods of stable condition (remissions) and active manifestations (exacerbations). Assessment of activity and identification of prognostically unfavorable factors is the main task in monitoring patients with SLE, however, the "golden the standard" has not yet been developed. Existing methods determine either the activity of SLE at the time of examination and the dynamics of this parameter during observation and treatment, or the development of irreversible damage. The assessment of the severity index (IT) of the disease allows you to combine all the components. The aim of the study was to assess the clinical significance and prognostic informativeness of IT in patients with SLE. Material and methods. 146 male patients with a reliable diagnosis of SLE aged 15 to 64 years, observed over a 15-year period, were analyzed. The patients underwent a generally accepted clinical, laboratory and instrumental examination using standard methods for assessing the activity of the disease. To characterize the course and outcomes of SLE, IT and the SLICC/ACR Damage Index (SDI) were used. IT and damage index for the 1st, 5th, and 10th years of the disease were analyzed in dynamics in 133, 91, and 63 patients, respectively. Results. Significant correlations were found between IT at the time of activation and indicators reflecting the course and activity of SLE. The analysis of IT dynamics showed that during the first 5 years of the disease, its maximum increase was observed in patients with SLE onset age <20 years. In combination with SLE and secondary antiphospholipid syndrome, there was a more pronounced increase in IT compared to patients who did not have such disorders. The highest survival rates were observed in patients with "early" IT equal to 0. Conclusion. IT is a good indicator reflecting the "accumulated" activity of the disease. It increases with an increase in the prescription of the disease, while its increase can occur at any stage of the disease. This dynamics depends on the course of the disease, the timing of diagnosis, and concomitant pathology. IT correlates well with the indicators of activity and damage traditionally used in SLE, as well as the frequency of exacerbations of the disease, which indicates the possibility of using IT as a prognostic marker.
Keywords: systemic lupus erythematosus; monitoring of patients; assessment of activity and damage; severity index; prognosis.